Liderança e indicadores de desempenho da equipe de acesso e vendas institucionais da indústria farmacêutica no Brasil - Pappini Junior, Carlos (2012)
This study aims to analyze the role of leadership and implementation of performance indicators to teams of access of the pharmaceutical industry that meet the segment of institutional payers of medicines, be they the government, HMO´s or large companies. The dynamics of this new structure of business is configured in the model B2B, Business to Business, i.e. on the establishment of trade relations corporate as opposed to the traditional model doctor-patient-pharmacy, called in the scope of this study, such as B2C, Business to Consumer. The field research was carried out by means of personal interview, through of a questionnaire pre-prepared with a part of questions interrogations and other multiple-choice. The sample consisted of six leaders of the team of six different pharmaceutical industries, all multinationals and with high representatives of the turnover of the segment, which provides a relevant basic research. In the results, it was highlighted the lack of indicators consistent in order to measure in an efficient manner the performance of the teams. At the same time, we perceive a dichotomy in the role of leadership in this new dynamic of business and of the team, since the leaders surveyed have strengthened in general lines the need to delegate and to act in a more strategic to have a team with a profile more experienced, but at the same time, it was presented a discomfort with the absence of mechanisms to control more solid as their own performance indicators. In the absence of indicators it becomes imperative higher qualification and maturity of the leaders and the team